MEMBANGUN PENGETAHUAN DAN KESADARAN HUKUM MASYARAKAT DALAM MEMAHAMI BANTUAN HUKUM MELALUI PEMANFAATAN LKBH UBB - Ndaru Satrio; Sintong Arion Hutapea; Toni Toni (Jurnal Al Basirah, 2021)
Legal socialization with the theme Building Community Legal Knowledge and Awareness in Understanding Legal Aid through Utilization of LKBH UBB found that participants, in this case inmates at the Class IIA Pangkalpinang Narcotics Correctional Institution (Pangkalpinang Narcotics Prison), were not fully aware of legal aid. The positive impacts of the implementation of this legal socialization include: (1) knowing technically or procedurally legal aid; (2) find out further legal remedies that can be pursued further based on the criminal procedure law; (3) knowing the problems that may arise in the provision of legal aid, so that the community in general and the assisted members in particular can prevent this from happening. The methods used are: (1) explaining the legal aspects related to the legal basis of legal aid which is the obligation of the state; (2) explain the purpose of legal aid; (3) explain the important elements in the implementation of legal aid; (4) The socialization of the law is carried out in the form of lectures and in-depth interactive discussions at the Class IIA Pangkalpinang Narcotics Correctional Institution (Pangkalpinang Narcotics Prison); (5) Dissemination of legal socialization materials which essentially contain the legal basis for legal aid, the purpose of legal aid, elements of legal aid, ethics in the administration of legal aid.